If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -2) = 16 Reorder the terms: -3(-2 + x) = 16 (-2 * -3 + x * -3) = 16 (6 + -3x) = 16 Solving 6 + -3x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -3x = 16 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = 16 + -6 -3x = 16 + -6 Combine like terms: 16 + -6 = 10 -3x = 10 Divide each side by '-3'. x = -3.333333333 Simplifying x = -3.333333333
| t^2-2t-120=0 | | 3x+x=130 | | 3(n+5)+2=60 | | 4w-6= | | .20*40= | | n^2=6n+72 | | b/4+5=14 | | x+y=130 | | a/9=6 | | -7=11+x | | 2x-5x=-6 | | 3*76= | | (9x-81)=12 | | 34/6=2x+1/3 | | 3x^2-2x-12x+8= | | 3x+y=130 | | 6y=30y+140 | | 2abc+d=3 | | -5y-2y+3y=9 | | -19-(-4)=x | | -10-(-5)=x | | -18=6x-4x | | 3/4=z/16 | | 2a+-5b+5a+-1b= | | c^2=40-3c | | 8x-9+7x= | | 55=5/9(f-32) | | 7-3x=5x | | 2a-7=1 | | 3(x+3)=4(x-1) | | (-3y+18)=y | | 4a-6(a+1)=2(a+5) |